Standardization of the bio-active compounds (rotenoids) from the extract of local plant species (derris elliptica) using the internal standard method of high performance liquid chromatography (HPLC) - Saiful Irwan, Zubairi; M. R., Sarmidi; R. A., Aziz (2005)
It is well known now that some plant species represent an efficient factory of chemicals, which are manufactured and used as bio-weapons against pest attacks. Extensive work has been done during the last few decades on these potentially useful compounds. During the last few decades a growing interest has been paid for safe agricultural production i.e free residual toxicity hazards to human beings and to the environment. Plant extracts-based biocides possess a great advantage compared with the chemical ones. Their efficacies are also acceptable. Research carried out was to standardize and determine the bio-active compounds from the extract of local plant species (Derris elliptica) using the internal standard method of the isocratic High Performance Liquid Chromatography (HPLC) analysis system. The raw plants were collected from Kota Johor Lama, Johor and sorted to collect the root and stem. Only the root and stem were utilized as a raw material of the extraction process. The root and stem were extracted by using the Normal Soaking Extraction (NSE) method at 28 0C to 30 0C with 95.0 % (v/v) of acetone as a solvent and the solvent-to-solid ratio of the extraction is (10.0 ml/g). The extraction was carried out for 24 hours and further cleaned up to remove fine debris of root and stem prior to determination of the rotenone and its derivatives content. The rotenone cube resin of SAPHYR S.A.R.L (France) was used to verify the appearances of the compounds in the extract. The employed method of analysis shows significant appearances of the bio-active compounds in the extract compared with the commercial grade of rotenone cube resin.